2021
DOI: 10.1111/ene.14862
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐sectional area reference values for peripheral nerve ultrasound in adults: A systematic review and meta‐analysis—Part III: Cervical nerve roots and vagal nerve

Abstract: Background and purpose Measurement of the cross‐sectional area (CSA) of cervical nerve roots using ultrasound is useful in the evaluation of inflammatory polyneuropathies, and measurement of CSA of the vagal nerve might give information about involvement of the autonomic nervous system. We performed a systematic review and meta‐analysis of published CSA reference values for cervical nerve roots and vagal nerve. Methods We included available‐to‐date nerve ultrasound studies on healthy adults and provide meta‐an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…However, this fraction might even be underestimated as high cutoff values for enlarged CSAs in comparison to other studies were applied. 23 Nevertheless, comparable studies on patients with CIDP found pathologic ultrasound findings with similar frequencies (64-89%). [24][25][26] In our study, abnormalities on nerve ultrasound were observed in four out of seven patients with Sjögren's syndrome and clinical signs of neuropathy but without neurophysiologic evidence of neuropathy.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…However, this fraction might even be underestimated as high cutoff values for enlarged CSAs in comparison to other studies were applied. 23 Nevertheless, comparable studies on patients with CIDP found pathologic ultrasound findings with similar frequencies (64-89%). [24][25][26] In our study, abnormalities on nerve ultrasound were observed in four out of seven patients with Sjögren's syndrome and clinical signs of neuropathy but without neurophysiologic evidence of neuropathy.…”
Section: Discussionmentioning
confidence: 84%
“…In our analysis, 72% of patients with Sjögren’ syndrome and suspected neuropathy showed abnormal findings on nerve ultrasound. However, this fraction might even be underestimated as high cutoff values for enlarged CSAs in comparison to other studies were applied 23 . Nevertheless, comparable studies on patients with CIDP found pathologic ultrasound findings with similar frequencies (64–89%) 24–26 .…”
Section: Discussionmentioning
confidence: 84%
“… 13 , 14 , 24 However, the VN CSAs in HCs did not vary significantly between age, gender, height, weight, and races in adults according to a systematic review and meta‐analysis. 25 …”
Section: Discussionmentioning
confidence: 99%
“…Both aspects might influence the sonographic pattern of peripheral nerve enlargement, which makes our results valuable as they represent daily clinical life (12,17,23,24). We did not analyze data of height, body weight, and age, as the effects of these demographic data on CSA are still under discussion (25)(26)(27)(28).…”
Section: Strengths and Limitationsmentioning
confidence: 99%